A beautiful mind. - Howard, Ron (Dreamworks Pictures/Universal Pictures, 2001)
Winner of 4 Academy Awards, including Best Pictures, A Baeutiful Mind is directed by Academy Award Winner Ron Howard and produced by his long time partner, Academy Award winner Brian Grazer. A Beautiful Mind stars Russell Crowe in an astonishing performance as brilliant mathematician John Nash, on the brink of international acclaim when he becomes entangled in a mysterious conspiracy. Now only his devoted wife (Academy Awards winner Jennifer Connelly) can help him in this powerful story of courage, passion and triumph.